Revitalisasi Kelembagaan BUMDes Melalui Pemberdayaan Masyarakat dalam Upaya Penguatan Ekonomi di Desa Gunturmekar Kabupaten Sumedang: Institutional Revitalization of Village-Owned Enterprises Through Community Empowerment in Efforts to Strengthen the Economy in Gunturmekar Village, Sumedang Regency - Wahidah, Idah; Eryanti, Devi; Haikal, Muhammad Alif (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The existence of BUMDes in Gunturmekar Village is still not a concern for village officials to be used to increase village income, apart from that, the existence of tourist destinations is still managed by third parties which opens up the possibility of synergy. Through community service carried out using lecture methods, demonstrations, and intensive guidance and collaboration with partners, namely DPMD, to provide assistance to BUMDes and build community understanding so that they take part as subjects in the development of BUMDes and make tourist destinations one of the business unit. After assisting, currently, the BUMDes business unit has a new business unit, namely a tourism village, and makes a positive contribution to village income.